Kompensasi, Motivasi Kerja dan Disiplin Kerja Sebagai Prediktor terhadap Kinerja Karyawan - Romagia , Mandataris (JIAGANIS, 2017)
ABSTRACT Variable in this research include free variable, namely Compensation (X1), motivation (X2), Discipline (X3), and the dependent variable is employee performance (Y). formulation of the problem in this study is whether the compensation, motivation, and discipline has a predictor of the performance of employees of PT. Telkom Tbk. BatamThis study uses quantitative data derived from primary data collected through questionnaires. The population in this study were all employees of as many as 105 people and sampling using the formula Slovin. Methods of data analysis used in this study is the use test instrument calibration is made by testing the validity and reliability. Data were analyzed using quantitative analysis method, the validity, reliability, normality test, multicolinearity, heteroscedasticity test, autocorrelation test, multiple regression analysis, T test, F test, test the coefficient of determination R2.Based on the results of data analysis showed that the variable compensation has a significant influence on the performance by t sig of 0.035 <0.05, motivational variables have a significant influence on the performance of the test value t sig 0.025 <0.05, and variable work discipline also has a significant influence on the performance of the test value t sig of 0.000 <0.05.Based on the results of test calculations F, together variable compensation, motivation, and discipline have significant effects on work performance with the value of F sig 0.000 <0.05. Keywords: Compensation, Motivation, Discipline, Performance